The Book Reads You: William Melvin Kelley's Typographic Imagination. - Nishikawa, Kinohi (American Literary History)
The experimental novelist William Melvin Kelley has confounded critical efforts to situate his work within the aesthetic and political parameters of Black Arts. Though Kelley was a contemporary of the movement, he wrote fiction that undermined its belief that literature ought to serve as a mouthpiece for "the people." Yet Kelley's two late novels, dεm (1967) and Dunfords Travels Everywheres (1970), evinced the same qualities of performative textuality that Black Arts practitioners had advanced for their cause. By directing his publisher to follow his typescripts as closely as possible, Kelley created typographic experiments that made blackness a feature of readers' engagement with the printed details of certain pages. Despite this convergence with Black Arts literary strategies, Kelley remained a maverick in the uses he identified for such experiments. Like other postmodern satirists of the era, he was a critic as much of racial indivisibility among blacks as he was of race's invisibility to whites. In his late fiction, then, Kelley used typographic play to subvert not only racial but class assumptions about what a "black" voice ought to sound like.